Beyond the stage: A study of motivations and promotional strategies driving Gen Z's attendance at Isyana Sarasvati's concerts - Putri Kusumaningrum, Anisa; Sugiono, Edi; Lestari, Rahayu (Indonesian Journal of Business, Accounting and Management, 2024)
This study aims to explore the impact of motivational factors associated with the Isyana Sarasvati Live in Concert event at Istora Senayan on Generation Z's interest in attending live music events. Specifically, it investigates (a) the influence of concert motivation on Gen Z's attendance, (b) the effects of promotion mix strategies on their attendance. Utilizing a quantitative research design, data were collected from a sample of 100 respondents who attended the concert. The findings indicate that both motivational factors and promotion mix strategies significantly and positively influence Gen Z's attendance interest. This research highlights the importance of understanding these dynamics to effectively engage and attract younger audiences to live music events. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.